Cryobanking: the New Noah's Ark for diverse medicinal and aromatic plants - Uchendu, E.E.; Akomolede, O.; Abberton, M. (Springer, 2025)
Plants with medicinal and aromatic values have been in use for centuries across the cultures and traditions of the world to treat illnesses, prevent ill health and produce fragrances. The World Health Organization (WHO) reported that 80% of people in developing regions depend on plant-based medicines for treatment of several recalcitrant diseases; thus there is a need to document effective conservation techniques to secure the future of propagules with short lifespans in order to reduce loss of the plants’ biodiversity. This compilation provides information on the available conservation methods, particularly in vitro long-term conservation protocols through cryopreservation for several medicinal plant types, and covers diverse explants. Medicinal and/or aromatic plants can be preserved using medium-term storage (MTS) or long-term storage (LTS). Both in vitro methods of conservation are crucial for safeguarding the plant species biodiversity, especially those of unique, rare, endangered and at-risk status. The in vitro methods rely on the principles of cellular totipotency during micropropagation. Ensuring that the germplasm is in good physiological status (optimal) prior to or during in vitro conservation is important toward the maintenance of quality and therapeutic properties. This review provides vital information toward the long-term conservation of medicinal plants while also highlighting the critical factors that affect successful cryopreservation.